Revisión de la historia y aplicación de escuaramida en organocatálisis - Hernández, Eduardo Hipólito; Romero-Ceronio, Nancy; Alvarado-Sánchez, Cuauhtémoc; Lobato-García, Carlos E.; Vilchis-Reyes, Miguel A.; Roa de la Fuente, Luis Fernando (Revista Científica, 2018)
Squaramide and its derivatives represent an important group of substances that are currently being successfully applied in asymmetric organocatalitic strategies, which is why this contribution presents a summary of the state of the art related to the synthesis of escuaramide derivatives and their role as chirality inducers in relevant synthetic sequences. To this end, a process of systematic search and selection of reports published in specialized journals of the area was established in order to present the most significant aspects of synthesis and the application of escuaramide derivatives in this key area of organic chemistry.